Improved formulation for admittance of thin and short monopole driving from coaxial line into dissipative media. - You, Kok Yeow; Abbas, Zulkifly; Khalid, Kaida; Kong, Ngoon Fah (Institute of Electrical and Electronics Engineers (IEEE), 2009)
An improved formulation of the admittance equation for small and thin monopole is presented where the coefficient of the capacitive correction term can be calculated directly from the values of the inner and outer radius of the coaxial line. The results were found to agree well with measurements and the finite element method (FEM). Some rules, features, and limitations of the improved formula are also discussed.